RESEARCH OF VEHICLE GROUPS MOVEMENT PARAMETERS ON THE TRANSPORT NETWORK OF CITIES: Array - , Н. О., Є. Б. (Municipal economy of cities. Series: «Economy science», 2018)
Due to the sharp increase in quantity of cars on the transport network of Ukrainian cities, which is currently overloaded, the subsequent introduction of technical means of traffic control leads to an increase in quantity of regulated local facilities that form groups of vehicles. The main mode of movement of vehicles on a network of cities becomes group, which leads to a change of character of distribution and traffic flow parameters, but despite the obvious influence of such a regime on the organization and traffic safety, its parameters have not been studied enough.The goal is to determine and clarify the distribution law of the main parameters that characterize group movement at high flow intensity, namely: dynamic dimension of vehicles, intervals between cars, speeds of vehicles in a group and their quantity, group size and its change during movement.Experimental researches of traffic on the road network were performed using video during periods of maximum loading. The results were processed using the methods of mathematical statistics and regression analysis.According to experimental results there were obtained the logarithmic normal probabilistic law of time intervals distribution in groups of dense traffic flows, the specific intensity of which exceeds 600 vph; the changes in basic characteristics of the vehicles group in the traffic flow when driving through the road crossing taking into account its intensity and the distance from the group forming object are determined. As well as, the distribution of hourly size of groups, the distribution of vehicle speeds in groups, hour and metric intervals between cars were obtained. A comparison of the experimental values of the intervals of movement of vehicles in the group and the calculated data of the safety distance, depending on the speed of movement were hold.Originality lies in the fact that the patterns of movement of groups of vehicles of dense traffic flows of high specific intensity on short sites are investigated.Increase of efficiency and traffic safety of vehicles on a road network is possible at introduction of automated control systems. They will allow to control traffic flows on the basis of information on traffic flows. The obtained research results can be used in the implementation of automated traffic control systems. Keywords: street-road network, traffic flow, traffic parameters of groups of vehicles.